Perancangan Aplikasi Penyewaan Virtual Office (VO) Pada PT. Berkah Sinergi Keluarga Konsultindo Berbasis Web - Ega Lusiyana; Iskandar Zulkarnain; Hany Maria Valentine (FIKOM - Bung Karno University, 2022)
PT. Berkah Sinergi Keluarga Konsultindo or Quickle Permit is a virtual office (vo) service provider engaged in law and services located in South Jakarta. Based on the research that has been done by the author through direct observation of the company, it is known that PT. The blessing of the Synergy of the Konsultindo Family experienced an increase in the number of virtual office (vo) service users. Until 2022, service users from PT. Thanks to the Synergy of the Konsultindo Family, there are already 214 companies that use the virtual office (vo) service. Of the many virtual office (VO) rental orders, there is no system that can manage information about the availability of virtual office (VO) packages, prices, facilities, and problems in processing rental or client data that make current clients complain about some of these problems. The stages of system development in making this information system use the SDLC method and programming language (PHP) and with MySQL for data storage. With the web-based virtual office (VO) rental information system that we created, we will handle these problems by assisting clients in viewing information related to virtual offices (VO) and ordering virtual office (VO) rentals without having to come directly to the company and making it easier for clients to access information on availability of virtual office (VO) packages and make.